2018
DOI: 10.1021/acs.jpca.8b07713
|View full text |Cite
|
Sign up to set email alerts
|

Hydration of Atmospheric Molecular Clusters II: Organic Acid–Water Clusters

Abstract: Using computational methods we study the gas phase hydration of three different atmospherically relevant organic acids with up to 10 water molecules. We study the dicarboxylic acid (pinic acid) and a tricarboxylic acid (3-methyl-1,2,3-butanetricarboxylic acid (mbtca)) that are both identified as products from α-pinene oxidation reactions. We also study an 2-oxohexanediperoxy acid (ohdpa) that have been identified as a product from cyclohexene autoxidation. To sample the cluster structures, we employ our recent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 56 publications
2
42
0
Order By: Relevance
“…This is the first study reporting the hygroscopic properties of MBTCA. A previous study showed that MBTCA was not hydrated significantly in the ambient atmosphere (Kildgaard et al, 2018), implying that the MBTCA solids stay in the air once they effloresced, based on our results.…”
Section: Hygroscopic Behavior Of Pure Mbtca Particlessupporting
confidence: 80%
“…This is the first study reporting the hygroscopic properties of MBTCA. A previous study showed that MBTCA was not hydrated significantly in the ambient atmosphere (Kildgaard et al, 2018), implying that the MBTCA solids stay in the air once they effloresced, based on our results.…”
Section: Hygroscopic Behavior Of Pure Mbtca Particlessupporting
confidence: 80%
“…Regarding the first requirement, we apply efficient generalized-gradient-approximation density functional theory with density fitting for the optimization of solvent-solute clusters, but note that semi-empirical quantum chemical methods [60] can very much reduce the increasing computational cost caused by considering solvent molecules explicitly. [39,59] As these methods struggle to properly describe important interactions in solution such as dispersion and hydrogen-bonding, corrections have been developed to alleviate such shortcomings. [61][62][63] Hence, their application for the conformational sampling of large clusters will be beneficial.…”
Section: Full Automationmentioning
confidence: 99%
“…In carboxylic acid dimers, the hydrogen bond donors and acceptors are saturated, which means that carboxylic acids are unlikely to form larger clusters than dimers (Vawdrey et al, 2004;Elm et al, 2014Elm et al, , 2019. Computational studies (Aloisio et al, 2002;Weber et al, 2012;Kildgaard et al, 2018) have shown that, in the gas phase, the energetically most favorable dihydrate is formed by two water molecules attaching to the same carboxylic acid group. Therefore, adding a second water molecule to the cluster does not significantly change the probability distribution of the screening charge density (σ profile) of the acid in the cluster compared to the acid in a monohydrate or dimer.…”
Section: Input File Generationmentioning
confidence: 99%
“…Group contribution methods, such as UNIFAC (Fredenslund et al, 1975) and AIOMFAC (Zuend et al, 2008), are often used to estimate activity coefficients of atmospherically relevant compounds. More recently, a quantumchemistry-based COnductor-like Screening MOdel for Real Solvents (COSMO-RS; Klamt, 1995;Klamt et al, 1998;Eckert and Klamt, 2002) has been used to predict thermodynamic properties of multifunctional compounds. Solubilities and activity coefficients of carboxylic acids have also been estimated using the COSMO-RS theory implemented in the COSMOtherm program (COSMOtherm, 2019).…”
Section: Introductionmentioning
confidence: 99%